Yu-Gi-Oh! Arc-V. 6 - Yoshida, Shin; Neufeld, Sarah, (Translator); Werry, John (Translator) (Shonen Jump manga., 2019)
Action Duels have become a global sensation, but what is the dark secret behind them that threatens to destroy the world? Yuya and his friends have infiltrated Eve<U+2019>s Antarctic base! In the space between dimensions, Reiji meets Adam at last and learns the truth about G.O.D. Elsewhere, Yuya squares off against Eve for a final Duel. What secrets will be revealed in this last battle?